Awareness and Associated Correlates of Contraception Use among Patients of Reproductive Age: A Cross-sectional Analysis at Jinnah Postgraduate Medical Centre, Karach - Haider, Syeda Zehra; Zaidi, Tafazzul Hyder; Sajid, Benish; Haider, Summaiya; Tabassum, Rizwana; Jafry, Mishal; Saleem, Sunila; Abbas, Kiran (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the level of awareness of contraception among patients of reproductive age groups.Study Design: Cross-sectional analytical study.Place and Duration of Study: Jinnah Postgraduate Medical Centre, Karachi Pakistan, between Jul 2018 to Jul 2019.Methodology: Women aged more than 18 years and not disoriented at the time of data collection were included in the study. Women younger than 18 years or those getting treatment for psychiatric illnesses or amenorrhea were excluded from the study. A predefined proforma was used to collect data from the study participants.Results: The mean age of the female patients was 26.5±8.6 years. The awareness regarding contraception was seen in 207(64.2%) female patients. Notably, 190(59.1%) women were aware of contraceptive methods. 210(65.3%) of the female patients considered contraception a safe practice. 225(69.7%) female patients thought contraception was necessary for child spacing. 82(25.4%) female patients had used some contraceptive at least once in their lifetime. Most women use oral contraceptive pills because of their easy-to-use and inexpensive features. Age and marital status significantly associated with the degree of awareness among participants (p